PENGARUH LABELISASI HALAL, HARGA DAN KUALITAS PRODUK TERHADAP PEMBELIAN MIE INSTAN IMPORT - Winny Alna Marlina; Sinta Huliskia; Nur Ari Sufiawan (Management Insight: Jurnal Ilmiah Manajemen, 2025)
In Payakumbuh, there are lots of Instant Noodles circulating, ranging from local and imported products. The most popular imported noodle by students of the Faculty of Economics and Business, Andalas University, is Samyang Noodle from Korea. Although the price of this noodle is more expensive, many students buy this product. The purpose of this research is to find out whether the halal label, price, and product quality affect the decisions students make to buy certain items. Quantitative research methods with surveys. This study uses the coefficient of determination and multiple linear regression to analysis the data. The number of research samples is 154 samples. Research locus at the Payakumbuh Campus, Andalas University. The results of research on halal labeling, price, and product quality have a positive effect on purchasing decisions for imported instant noodles (Mie Samyang) for students of Andalas University, Payakumbuh Campus, Management Department.